2012
DOI: 10.1016/j.jhazmat.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic-enhanced bioaugmentation for remediation of chlorinated solvents contaminated clay

Abstract: Successful bioremediation of contaminated soils is controlled by the ability to deliver bioremediation additives, such as bacteria and/or nutrients, to the contaminated zone. Because hydraulic advection is not practical for delivery in clays, electrokinetic (EK) injection is an alternative for efficient and uniform delivery of bioremediation additive into low-permeability soil and heterogeneous deposits. EK–enhanced bioaugmentation for remediation of clays contaminated with chlorinated solvents is evaluated. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low‐permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low‐permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
“…A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE. These results are comparable to the electromigration rate of bromide (3.3 cm/day) measured in column studies using low‐permeability site soils by Cox et al ().…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
“…If the environmental conditions do not support microorganisms growth, electrokinetic can transmit a number of nutrients, electron acceptors, complexing agents, and also surfactant to microorganisms so biodegradation limitation in soil can be reduced (Annamalai et al, 2017;Da Rocha et al, 2009;Guo et al, 2014;Li et al, 2012b;Luo et al, 2006;Mena et al, 2016c). Several researches also suggest that microorganisms can be flushed into soil to improve removal efficiency because indigenous microorganisms can not treat hydrocarbon contaminants effectively (Asgari et al, 2013;Kim et al, 2005;Mao et al, 2012).…”
Section: Biodegradationmentioning
confidence: 99%
“…Recent study showed that microorganisms can be transported by electrokinetics in sand via electrophoresis and the microorganisms remained active and viable after the transport process [42]. Another study showed that by adding bacteria in the anode and cathode compartment bacteria was transported via electroosmotic flow in clay soil [43]. However, in general, bioaugmentation studies have not been successful.…”
Section: Bioaugmentationmentioning
confidence: 99%